2008
DOI: 10.1364/ao.47.003980
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nanosecond laser induced fluorescence of in vitro seawater phytoplankton

Abstract: Seawater has been irradiated using a train of 70 ns flashes from a 440 nm laser source. This wavelength is on resonance with the blue absorption peak of Chlorophyll pigment associated with the photosystem of in vitro phytoplankton. The resulting fluorescence at 685 nm is instantaneously recorded during each laser pulse using a streak camera. Delayed fluorescence is observed, yielding clues about initiation of the photosynthetic process on a nanosecond time scale. Further data processing allows for determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The fluorescent lifetime of chlorophyll can vary between 0.3 [6] and 10 ns [7] depending on various factors such as temperature, concentration and the overall condition of the Chlorophyll sample. A realistic minimum target of 1.0-2.0 ns is taken as it correlates well with the fast fluorescent lifetimes typical with chlorophyll-A in seawater samples described in [13]. In typical phase fluorometers, optimal noise immunity is obtained for excitation frequencies that are related to the fluorescent lifetime under study by the relationship (8) which, for this application, gives an optimal frequency of 79.6 MHz.…”
Section: A Custom Tia Integrated Circuitmentioning
confidence: 99%
“…The fluorescent lifetime of chlorophyll can vary between 0.3 [6] and 10 ns [7] depending on various factors such as temperature, concentration and the overall condition of the Chlorophyll sample. A realistic minimum target of 1.0-2.0 ns is taken as it correlates well with the fast fluorescent lifetimes typical with chlorophyll-A in seawater samples described in [13]. In typical phase fluorometers, optimal noise immunity is obtained for excitation frequencies that are related to the fluorescent lifetime under study by the relationship (8) which, for this application, gives an optimal frequency of 79.6 MHz.…”
Section: A Custom Tia Integrated Circuitmentioning
confidence: 99%
“…A modified bioluminescence sensor described by Herren et al (2005), for example, can now sample at 60 Hz, which would improve the horizontal resolution by at least an order of magnitude. An ultra-high sampling frequency chlorophyll a fluorometer is also under development for the AUV (Bensky et al, 2008), which would have a significant effect on resolving the micro-scale. Although technically challenging, the installation of calibrated multi-frequency echosounders on AUVs, has the potential to improve the measurement of the horizontal extent of thin layers.…”
Section: Sampling and Spatial Scales Of Layersmentioning
confidence: 99%
“…yellow substance and pollutants. Bensky et al [17] observed instantaneous fluorescent emission from Chlorophyll in phyto-plankton resident in vitro seawater samples as a result of pumping with a 440 nm, 70 ns laser pulse.…”
Section: Introductionmentioning
confidence: 99%